Measurement of resonant field imaging aura for human waves / Zunairah Murat and Mohd Nasir Taib - Murat, Zunairah; Taib, Mohd Nasir (2003)
This research shows the usefulness of a Resonant Field Imaging System. The understanding of bioenergy (Aura) and Chakra system and its relationship with the human body were obtained from the frequency measurement at 36 various point of human body and brain aura using RFI System. The software then prints out the scientific information and objective interpretations for all Auras and bioenergy fields and also identifies the type and functions of all bioenergy present in specific regions of the human brain. The results show the psychology and physiological state of the female students and male students including left and right brain dominant.